Review of the Fund's Strategy on Overdue Financial Obligations. (Policy Papers; Policy Paper, 2008)
This paper reviews progress under the Fund's strengthened cooperative strategy on overdue financial obligations. Total arrears to the Fund declined by SDR 552 million since the last review, owing largely to the clearance of arrears by Liberia in March 2008. While Sudan's payments in excess of its new obligations falling due to the Fund also contributed to the decline, arrears by Somalia and Zimbabwe increased further. The majority of the arrears to the Fund (85 percent) were to the General Resources Account (GRA).